Privileged wills and the application for probate in Malaysia: a legal study / Faridah Hussain - Hussain, Faridah (Universiti Teknologi MARA, 2020)
Privileged wills may be made informally. An application for probate may be filed if soldiers, airmen and sailors die leaving privileged wills. Soldiers and airmen in actual military service may make a privileged will.Similarly" sailors (including members of the naval forces) being at sea may make privileged wills. This paper aims to highlightthe mode of making an application for probate in privileged willscase. Using qualitative method and comparative analysis, this paper analyses the provisions of the law on privileged wills under the Wills Act 1959, Sabah Wills Ordinance, Armed Forces Act 1972, Merchant Shipping Ordinance 1952, Muslim Wills (Selangor) Enactment 1999, Muslim Wills (Negeri Sembilan) Enactment 2004, Muslim Wills (Malacca) Enactment 2005, Kelantan Muslim Wills Enactment 2009 andMuslim Wills Enactment 2017 (Pahang).Besides, case reports, journal articles and textbooks are analysed.The law relating to privileged wills in Malaysia which allow for non-compliance with the formalities in the execution of a will may lead to fraud. This paper examines whether there is a need to formulate a new form for filing an application for probate for privileged wills cases in Malaysia. This paper argues that the new form for an application for probate for privileged wills cases is necessary to help the applicant in proving the privileged wills made by privileged personnel in Malaysia.